Prevention of Contrast-Induced Nephropathy through a Knowledge of Its Pathogenesis and Risk Factors. (3rd December 2014) - Andreucci, Michele; Faga, Teresa; Pisani, Antonio; Sabbatini, Massimo; Russo, Domenico; Michael, Ashour
Abstract : Contrast-induced nephropathy (CIN) is an iatrogenic acute renal failure (ARF) occurring after the intravascular injection of iodinated radiographic contrast media. During the past several years, in many patients undergoing computed tomography, iodinated contrast media have not been used for the fear of ARF, thereby compromising the diagnostic procedure. But recent studies have demonstrated that CIN is rarely occurring in patients with normal renal function and that preexisting chronic renal failure and/or diabetes mellitus represent(s) predisposing condition(s) for its occurrence. After the description of CIN and its epidemiology and pathophysiology, underlying the important role played by dehydration and salt depletion, precautions for prevention of CIN are listed, suggested, and discussed. Maximum priority has to be given to adequate hydration and volume expansion prior to radiographic procedures. Other important precautions include the need for monitoring renal function before, during, and after contrast media injection, discontinuation of potentially nephrotoxic drugs, use of either iodixanol or iopamidol at the lowest dosage possible, and administration of antioxidants. A long list of references is provided that will enable readers a deep evaluation of the topic.